Visnis apps / Nickolen Robot … [et al.] - Robot, Nickolen; Minsuan, Steve; Madinus, Viviana Nelynda; Jackline, Mohd Syahyril; Yahya, Ahmad Fareez (Faculty of Computer and Mathematical Sciences, 2022)
In 2019, Sabah Tourism Board stated that 54 percent of the tourist arrivals in Sabah were free independent travelers. This type of traveler does not rely on travel agents, yet the problem of getting lost in a foreign place persists. Therefore, we developed an application to assist it, with the objective of assisting independent travelers in managing their own trip arrangements. This application is a smart travel planner that will automatically build a comprehensive travel itinerary, give a route, and a map so that they will have direction and prevent getting lost, as well as promote the government's industrial digital transformation in the tourist industry. The novelty of our application is that user will only need to key in data such as budgets, areas, or districts they want to visit, include type of attraction. Then the application will sort out their itinerary based on the suitability of the route. After the itinerary is generated, the user can download and use it offline. It may also be used as a tourist guide by displaying the routes that will take them to the destination of their choice or the suggested tourist attractions in the region or district of their choice. The benefit of our application is that it immediately connects to the local community and local suppliers in the chosen location when the itinerary is generated. Furthermore, it can generate employment for the local people by engaging them as guides if the visitor just needs a guide for a certain location.